Modification of the PERT method for project time evaluation taking into account unexpected delays - Litvinov, Vladimir; Moskaliuk, Andrii (Eastern-European Journal of Enterprise Technologies, 2018)
The PERT-based method for estimation of project implementation time, which uses Rayleigh distribution instead of β-distribution, was proposed. The modification of the PERT, which made it possible to involve the quality of an expert into the assessment and to simplify the examination procedure was proposed. We offered a new method for project evaluation, based on the properties of Rayleigh distribution and taking into consideration the peculiarities of plotting a network diagram in IT- projects with a high degree of work detailing in the face of the existing possibilities of extending the time of particular tasks. Three different methods project time evaluation, based on two different statistics and two different methods for calculation of project time, were compared. Comparison was performed with the view to search for the simplest method in terms of information acquisition and suitable for algorithmic implementation. It was shown that the estimation result is more consistent with specificity of complex IT-projects and makes it possible to reduce the number of iterations within project implementation time, as well as to use an objective assessment of the main sources of errors in determining time, giving evaluation with the probability that was assigned beforehand. It was shown that the estimate of the most probable and minimum time of project completion during the calculation by the new method is consistent with the results of the calculations using the PERT method, while the evaluation of maximum time differs strongly, as the new method is more pessimistic in this sense, and it matches better the characteristics of complex IT-projects that have a high probability of unexpected delays during implementation. We draw conclusions on the possible application of results in creation of a project time evaluation system based on the methods of artificial intelligence, and determined parameters for setting such a system.